The Role of Heart Rate Recovery: Possibility of Heart Disease and Exercise Program Application - Hae Sung Lee; Jong-Hee Kim (The Korean Society of Animal Reproduction and Biotechnology, 2019)
Heart rate is a relatively simple and non-invasive method that is used as an important physiological indicator in many studies and has a close relationship with heart structure and function, cardiovascular disease and sudden cardiac death. In general, appropriately low heart rate during resting means effective heart function and cardiovascular fitness; heart rate at recovery is an important indicator of health and disease condition. We found a beagle dog (Dog_1) with a high heart rate in the previous preliminary experiment. Therefore, purpose of this study was to compare the heart rate response of the Dog_1 with the control group during 12 weeks of interval exercise, to evaluate the structural and functional abnormalities of the heart and to verify the applicability of exercise program. Heart rate was checked during 12 weeks of interval exercise, and after the exercise was over, imaging examination and hematological and serum biochemistry were performed. As a result, Dog_1 (165.6 ± 1.5) showed significantly higher heart rate in low intensity session of interval exercise than control group (133.3 ± 0.5, p < 0.01). In addition, Dog_1 (181.2 ± 1.4) showed significantly higher heart rate than control group (155.1 ± 0.9) in high intensity session (p < 0.01). The heart rate (30 sec, 60 sec) during recovery state was higher in Dog_1 (30 sec: 156.8 ± 4.0, 60 sec: 166.8 ± 5.8) than in the control group (30 sec: 111.2 ± 2.5, 60 sec: 104.0 ± 5.1, p < 0.01). The results of the imaging examination of Dog_1 with high heart rate confirmed that the heart had no functional and structural abnormalities. All beagles with the interval exercise program did not show maladjustment, and in the hematological and serum biochemistry results, all the parameter were within the reference range. If the interval exercise program of this study is used in the future, it is expected to be used as an important basic data to achieve the purpose of health, welfare, and physical fitness improvement of dogs.